Can new quality productive forces promote inclusive green growth: evidence from China - Wang, Qi; Chen, Xiayang (Frontiers in Environmental Science, 2024)
Inclusive green growth (hereafter “IGG”), as a green and intensive development mode that considers both fairness and efficiency, environmental protection and development, is crucial for achieving sustainable development. New quality productive forces (hereafter “NQPFs”) have become a novel and significant factor in promoting IGG. This study aims to examine the connection between NQPFs and IGG. Based on the data from 283 Chinese cities between 2010 and 2021, the “CRITIC-entropy value” objective combination weighting method is adopted to establish comprehensive indicator system of NQPFs and IGG in this paper. The spatiotemporal characteristics, mutual relationship and influencing mechanism of NQPFs and IGG are evaluated based on kernel density function, panel fixed effect model and spatial Durbin model. The results show that both NQPFs and IGG in China have shown a steady upward trend. NQPFs can significantly promote IGG, and economic agglomeration and technological innovation are important approaches to their interaction. In the period of high Internet penetration and in developed cities, the role of NQPFs in promoting IGG is more obvious. There is also a double threshold effect of financial development in this promotion process. With financial development improving, this promotion effect is significantly enhanced. Our research advocates promoting IGG by enhancing NQPFs, thereby protecting the earth’s ecological environment and attaining long-term sustainability of human society.